2020
DOI: 10.1111/jnc.14936
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus tropism for olfactory sensory neurons in mice

Abstract: The primary function of the respiratory tract is to exchange gases. The upper respiratory tract includes the nasal cavity, which plays a role in the detection of odorants via the olfactory neuroepithelium (Cole, 1954). Inhalation can also lead to the transmission of harmful environmental agents, such as bacteria and viruses. The inhaled microorganisms and particles first pass through the nasal cavity, which is covered in large parts by the respiratory epithelium. The olfactory epithelium is present in the caud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 49 publications
3
29
0
1
Order By: Relevance
“…[24]. In mice, HRSV-infected cells were mainly found in the olfactory mucosa, which was recently observed by another group as well [30]. The olfactory mucosa contains olfactory receptor neurons, which are a potential route to the central nervous system [31].…”
Section: Discussionmentioning
confidence: 66%
“…[24]. In mice, HRSV-infected cells were mainly found in the olfactory mucosa, which was recently observed by another group as well [30]. The olfactory mucosa contains olfactory receptor neurons, which are a potential route to the central nervous system [31].…”
Section: Discussionmentioning
confidence: 66%
“…Two recent reports indicate that olfactory neurons in hamster (Sia et al, 2020) and respiratory cells in ferret (Ryan et al, 2020) may be the target of SARS-CoV-2 but these studies did not focus on the nasal cavity and they did not use double staining to clearly identify the infected cells in the OE. We observed that SARS-CoV-2 can infect other nonneuronal cells in the nasal cavity, notably in the epithelium covering the lumen of Steno's gland which is however poorly described in the literature (Bryche et al, 2019b). Further studies are required to clearly identify the other non-neuronal cells infected by SARS-CoV-2 in the nasal cavity which may facilitate the systemic infection of other cell types and tissues lower in the respiratory airways.…”
Section: Discussionmentioning
confidence: 86%
“…We finally examined the presence of immune cells in the olfactory mucosa using Iba1+ as a specific marker of monocyte/macrophage lineage (Bryche et al, 2019b); (Fig. 4A).…”
Section: Infiltration Of Immune Cells In the Olfactory Epithelium Folmentioning
confidence: 99%
“…The axons of the olfactory neurons are a gate to the OB and provide a direct pathway to the CNS. Some viruses, like Influenza and Herpes simplex, exploit this olfactory pathway to access the OB, from which they can spread to other brain regions, as described in various animal models of infection [22].…”
Section: Discussionmentioning
confidence: 99%